Science Without Publication Paywalls: cOAlition S for the Realisation of Full and Immediate Open Access - Schiltz, Marc (Frontiers in Neuroscience, 2018)
In this Perspective, a group of national funders, joined by the European Commission and the European Research Council, announce plans to make Open Access publishing mandatory for recipients of their agencies’ research funding.